How to write and publish a scientific paper - Day, Robert A. (ISI, 1979)
To be useful, scientific research needs to be explained clearly to others--to colleagues, to administrators, to foundations and governmental bodies, and to the public. This thoroughly revised edition of the classic How to Write and Publish a Scientific Paper gives beginning scientists and experienced researchers alike practical advice on writing about their work and publishing what they write. The core of the book consists of a "how-to" guide to writing and publishing research articles for scientific journals, explaining every step of the process, from choosing a suitable journal for your work to presenting the results and citing references. In addition to the information on writing for scientific journals.